2015
DOI: 10.1104/pp.15.01082
|View full text |Cite
|
Sign up to set email alerts
|

Inference and prediction of metabolic network fluxes

Abstract: In this Update, we cover the basic principles of the estimation and prediction of the rates of the many interconnected biochemical reactions that constitute plant metabolic networks. This includes metabolic flux analysis approaches that utilize the rates or patterns of redistribution of stable isotopes of carbon and other atoms to estimate fluxes, as well as constraints-based optimization approaches such as flux balance analysis. Some of the major insights that have been gained from analysis of fluxes in plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 98 publications
1
46
0
Order By: Relevance
“…These studies usually examined photosynthetic performance in response to short‐term or long‐term changes in irradiance, and while they have generally reported only small perturbations in photosynthesis as a result of the change in AOX amount, they are nonetheless a body of work supporting the idea that this unique respiratory pathway may have a specific role in the photosynthesizing cell (Noguchi and Yoshida ). These finding are further supported by recent computational modelling studies of plant metabolism, some of which predict an increased contribution of AOX to respiration with increasing irradiance (Buckley and Adams , Cheung et al , Nikoloski et al ). Interestingly, a role of AOX in optimizing photosynthesis at high irradiance was also recently established for the diatom Phaeodactylum tricornutum , using an AOX knockdown approach (Bailleul et al ), and knockdown of AOX in soybean has also been shown to perturb photosynthesis (Chai et al ).…”
Section: Introductionsupporting
confidence: 62%
“…These studies usually examined photosynthetic performance in response to short‐term or long‐term changes in irradiance, and while they have generally reported only small perturbations in photosynthesis as a result of the change in AOX amount, they are nonetheless a body of work supporting the idea that this unique respiratory pathway may have a specific role in the photosynthesizing cell (Noguchi and Yoshida ). These finding are further supported by recent computational modelling studies of plant metabolism, some of which predict an increased contribution of AOX to respiration with increasing irradiance (Buckley and Adams , Cheung et al , Nikoloski et al ). Interestingly, a role of AOX in optimizing photosynthesis at high irradiance was also recently established for the diatom Phaeodactylum tricornutum , using an AOX knockdown approach (Bailleul et al ), and knockdown of AOX in soybean has also been shown to perturb photosynthesis (Chai et al ).…”
Section: Introductionsupporting
confidence: 62%
“…In an update on the current approaches for metabolic flux analyses, factors are compiled that determine the specific properties of a metabolic network as far as its stability and capability to maintain homeostasis is concerned (Nikoloski et al . ). In particular, the authors point out that more data are required so that the interrelationship of metabolite levels, fluxes and enzyme properties can be integrated into mathematical models.…”
Section: Introductionmentioning
confidence: 97%
“…Part of the energy that is dissipated through plant respiration is used during photosynthesis for the recycling of adenosine triphosphate (ATP; Silva et al, ) and never becomes available to drive metabolic processes in other parts of the plant (i.e., in heterotrophic plant cells). A fraction of ecosystem respiration is the result of plant metabolic expenses including biomass growth and intercellular transport of metabolites (Nikoloski et al, ). An increase in ecosystem photosynthesis, and thus energy accumulation, tends to be accompanied by an increase in respiration (i.e., energy dissipation; Baldocchi & Penuelas, ) such that the ratio of gross to net primary production is often approximated as a constant (Waring et al, ) but with substantial variability related to site and changes in meteorological conditions (Collalti & Prentice, ).…”
Section: Introductionmentioning
confidence: 99%